Normative values of the motor competence assessment (MCA) from 3 to 23 years of age. Issue 9 (September 2019) - Rodrigues, Luis P.; Luz, Carlos; Cordovil, Rita; Bezerra, Pedro; Silva, Bruno; Camões, Miguel; Lima, Ricardo
Abstract: Objectives: Growing evidence of the importance of motor competence for developing a healthy lifestyle has been established in the last decade. Nonetheless, no single instrument or observation tool have been able to fully measure this construct, particularly because most were built for the diagnosis of children in risk for motor impairment; are limited to a few years of the developmental span; lack objectivity in the assessment protocols; or do not include the locomotor, stability, and manipulative components. This led to the difficulty of comparing researches, and longitudinally follow children into adulthood. Recently, a novel proposal to assess motor competence was presented - the Motor Competence Assessment (MCA) - and this study aims to present the MCA normative data from 3-to-23 years. Design and methods: Two thousand and eighty-seven participants (1102 boys) between 3 and 23 years of age were evaluated in the MCA (standing long jump, 10 m shuttle run, throwing velocity, kicking velocity, lateral jumps, shifting platforms). Results for each test were introduced in the LMS Chartmaker 2.3. The best model for test and sex was used, resulting in normative curves and percentile values. Results: Final norms showed a good fit to the instrument developmental expectations, allowing to differentiate and classify performances along the age interval. Conclusions: The MCA age- and sex- normative values allow to assess motor competence from childhood to early adulthood. Future directions will include obtaining a total MCA score and the normative scores for the MCA components (stability, locomotion, object control), and to expand the norms to adulthood and old age.